Blood Transfusion and Survival for Resected Adrenocortical Carcinoma: A Study from the United States Adrenocortical Carcinoma Group. Issue 7 (July 2017) - Poorman, Caroline E.; Postlewait, Lauren M.; Ethun, Cecilia G.; Tran, Thuy B.; Prescott, Jason D.; Pawlik, Timothy M.; Wang, Tracy S.; Glenn, Jason; Hatzaras, Ioannis; Shenoy, Rivfka; Phay, John E.; Keplinger, Kara; et al.
Perioperative blood transfusion is associated with decreased survival in pancreatic, gastric, and liver cancer. The effect of transfusion in adrenocortical carcinoma (ACC) has not been studied. Patients with available transfusion data undergoing curative-intent resection of ACC from 1993 to 2014 at 13 institutions comprising the United States Adrenocortical Carcinoma Group were included. Factors associated with blood transfusion were determined. Primary and secondary end points were recurrence-free survival (RFS) and overall survival (OS), respectively. Out of 265 patients, 149 were included for analysis. Out of these, 57 patients (38.3%) received perioperative transfusions. Compared to nontransfused patients, transfused patients more commonly had stage 4 disease (46% vs 24%, P = 0.01), larger tumors (15.8 vs 10.2 cm, P < 0.001), inferior vena cava involvement (24.6% vs 5.4%, P = 0.002), additional organ resection (78.9% vs 36.3%, P < 0.001), and major complications (29% vs 2%, P < 0.001). Transfusion was associated with decreased RFS (8.9 vs 24.7 months, P = 0.006) and OS (22.8 vs 91.0 months, P < 0.001). On univariate Cox regression, transfusion, stage IV, hormonal hypersecretion, and adjuvant therapy were associated with decreased RFS. On multivariable analysis, only transfusion [hazard ratio (HR) = 1.7, 95% confidence interval (CI) 51.0–2.9, P = 0.04], stage IV (HR = 3.2, 95% CI = 1.7–5.9, P < 0.001), and hormonal hypersecretion (HR = 2.6, 95% CI = 1.5–4.2, P < 0.001) were associated with worse RFS. When applying this model to OS, similar associations were seen (transfusion HR = 2.0, 95% CI = 1.1–3.8, P = 0.02; stage 4 HR = 6.2, 95% CI = 3.1–12.4, P < 0.001; hormonal hypersecretion HR = 3.5, 95% CI = 1.9–6.4, P < 0.001). There was no difference in outcomes between patients who received 1 to 2 units versus >2 units of packed red blood cells in median RFS (8.9 vs 8.4 months, P = 0.95) or OS (26.5 vs 18.6 months, P = 0.63). Peri-operative transfusion is associated with earlier recurrence and decreased survival after curative-intent resection of ACC. Strategies and protocols to minimize blood transfusion should be developed and followed.